Chaining the Unchained Books: Copyright as an Infringement on the Philosophy of the Library Science - Ahuja, Ashish A. (DESIDOC Journal of Library & Information Technology, 2003)
This paper gives a brief overview of the philosophy and laws oi library science as propounded by Dr SR Ranganathan. Then it gives a brief introduction to the laws of copyright in lndia under the Copyright Act 1957 and the later ammendments in view of ongoing information revolution. It also explains what constitutes copyright protection and copyright infringement. http://dx.doi.org/10.14429/dbit.16.6.3287